The application of Build, Operate and Transfer (BOT) contract in Majlis Agama Islam Wilayah Persekutuan Malaysia - Mohd Yunus, Saidatolakma; Mohd. Noor, Azman (IIUM Press, International Islamic University Malaysia, 2017)
This Build, Operate and Transfer (BOT) is a new concept applied in developing and constructing private and public infrastructures. It is a means of project financing and operating practiced primarily in the area of private infrastructure in developing countries. Recently, some waqf institutions have applied the BOT approach. The BOT structure gives a new direction in the field of waqf, as it enhances waqf property for public benefits. The involvement of waqf institution in developing its property and public infrastructures through BOT is a challenging exercise. The study examines the current practice of this contract in waqf institutions in general and in Majlis Agama Islam Wilayah Persekutuan with reference to the contracts applied in compliance with the principles of Sharīah.